Experimental Transapical Endoscopic Ventricular Visualization and Mitral Repair - Ruttkay, Tamas; Czesla, Markus; Nagy, Henrietta; Götte, Julia; Baksa, Gabor; Patonay, Lajos; Doll, Nicolas; Galajda, Zoltan (The Thoracic and Cardiovascular Surgeon, 2015)
Background An increasing number of experimental beating heart animal studies describe simple transapical mitral valve repairs based on the direct endoscopic visualization of the left ventricle. The aim of our human cadaveric study was to develop a method for more complex transapical endoscopic procedures by on-pump heart operations.Materials and Methods After preparation of 20 human fresh cadavers, a standard left anterolateral minithoracotomy was performed in the fifth intercostal space and the pericardium was entered. A rigid 0 degree endoscope and the instruments were introduced through a silicon apical port. To restore the natural form of the left heart, CO2 was insufflated. To test the mitral valve competence, the left ventricle was pressure-injected with saline after each step. After transecting the chords of the A2 segment of the anterior mitral leaflet before the experimental mitral valve repair, the tendinous chord was replaced using an especially designed clip chord. The second part of the experiment consisted of a segmental excision of the P2 segment of the posterior mitral leaflet followed by a standard valvuloplasty and suture annuloplasty.Results With the help of the described transapical endoscopic mitral valve repair technique, we gained direct visual information of the coaptation line of the mitral leaflets as well as the anatomy and function of the subvalvular apparatus. Using intracardiac imaging, we could perform successful transapical complex mitral repair in each case.Conclusion The minimally invasive transapical endoscopic method has the potential to offer advantages for on-pump mitral valve repair procedures even in complex mitral valve repair cases.
Keywords: anatomy; minimally invasive surgery; mitral valve surgery